Energy and exergy recovery in a natural gas compressor station – A technical and economic analysis. (1st November 2015) - Kostowski, Wojciech J.; Kalina, Jacek; Bargiel, Paweł; Szufleński, Paweł
Highlights: Energy and exergy flow in a natural gas compressor station. Operational efficiency only 18.3% vs. 35.1% nominal. 3 energy/exergy recovery systems proposed. Up to 168.9 GW h/y electricity and 6.5 GW h/y heat recoverable. Legal obstacles: operators not allowed to produce electricity. Abstract: The paper presents possible solutions to improve the thermodynamic performance of a natural gas compressor station equipped with various type of compressor units and operated at part-load conditions. A method for setting a simplified energy and exergy balance based on the available metering information has been presented. For a case study plant, it has been demonstrated that the current part-load operation leads to a significant decrease in energy and exergy efficiency compared to the nominal state of machinery. Three alternative improvement strategies have been proposed: (1) installation of a heat recovery hot water generator for covering the existing heat demand of the plant; (2) installation of a heat recovery thermal oil heater for covering the existing heat demand and driving an organic Rankine cycle (ORC) for electricity generation; (3) installation of a heat recovery thermal oil heater with and ORC and gas expanders for switching into full-load operation of the gas turbine unit. Energy and exergy performance of the proposed strategies as well as their economic feasibility have been analyzed. The second scenario involving an ORC unit provides the highest local energy savings, however, its economic feasibility is not achieved under the current part-load operating conditions. A hypothetic scenario of the same station operated at full-load due to an increased gas transmission capacity demonstrate the economic feasibility (possible under optimistic price conditions). Finally, it has been shown that the possibility of waste energy recovery from natural gas transmission systems (in particular, from compressor stations) depends on legal regulations defining the status of the transmission network operator.